Tailoring and visualizing the pore architecture of hierarchical zeolites. (26th May 2015) - Wei, Ying; Parmentier, Tanja E.; de Jong, Krijn P.; Zečević, Jovana
Abstract : This review provides an overview of the different synthesis methods and microscopy techniques for tailoring and visualizing the pore architecture of hierarchical zeolites. Abstract : Recently the concept of hierarchical zeolites invoked more explicit attention to enhanced accessibility of zeolites. By realizing additional meso-/macroporosity with the intrinsic microporosity of zeolites, a hierarchical pore system arises which facilitates mass transport while maintaining the zeolite shape selectivity. A great number of synthesis strategies have been developed for tailoring the pore architecture of hierarchical zeolites. In this review, we give a general overview of different synthesis methods for introduction of additional porosity. Advantages and limitations of these different synthesis approaches are addressed. The assessment of pore structure is essential to build the link between the zeolite pore structure and its functionality. A variety of 2D and 3D microscopy techniques are crucial to visualize the hierarchical pore structure, providing unique and comprehensive information that, however, should be linked to the results of bulk characterization techniques as much as possible. The microscopy techniques are classified and discussed according to the different probes used, such as optical light, X-rays and electrons. Representative work is reviewed to elucidate the capability of each technique and their drawbacks.